SEJARAH BIROKRASI PENGADILAN PAKUALAMAN, 1878-1907 - Anggie Farizqi Prasadana, Muhammad; Nurhasanah, Ana (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
Pakualaman is one of the autonomous regions in Java that has an indigenous judicial institution. This institution requires bureaucracy to support the implementation of justice. The aim of this research is to understand the history of the Pakualaman Court bureaucracy from its inception to its demise. To obtain a comprehensive picture of the Pakualaman Court bureaucracy, historical research methods are required, consisting of topic selection, source collection, verification, interpretation, and writing. The research results show that the Pakualaman Court bureaucracy began to take shape during the reign of Paku Alam V and was abolished by the Dutch in the early 20th century. Throughout its existence, this bureaucracy was never free from Dutch intervention, which influenced various aspects of administration and policy.